Die Produktion besonderer Arbeitskräfte Auseinandersetzungen um den häuslichen Dienst in Österreich (1880-1938) - Richter, Jessica (De Gruyter, 2024)
The "servant question" in the late nineteenth century led to the proliferation of debates and conflicts regarding domestic work. Were household servants to be viewed as workers or as members of the household? How should their work be regulated and assessed? This volume examines these debates from multiple perspectives and discusses how domestic service had changed by the time Austria entered into Anschluss with the National Socialist German.